Hot stone massage therapy - mechanisms of the influence on the human organism of selected methods of use - Paweł Radziejowski (Kazimierz Wielki University, 2018)
A stone massage as a relaxing treatment combines the benefits of a relaxing massage, aromatherapy, thermotherapy and acupressure. The stone massage is a form of impact on the body which uses mechanical stimuli, the pressure on the tissue in order to induce physiological reactions. Therapeutic effects of stones was used hundreds years ago in the Far East. Women from that area applied hot stones on the stomach to reduce menstrual pain and other ailments. The 90's of XX century is a time of rebirth of hot stone massage, which first became popular in the United States of America. A modern hot stone massage is a treatment which perfectly complements physiotherapeutic activity which goal is the restoration of the damaged organs. What is more, it is also applied in wellness clinics, accelerating recreational processes, thus increasing the body's ability to exercise. It is worth mentioning that exist several methods of stone massage: dynamic massage, contrastive static and dynamic massage (several varieties) and static massage (energetic). More and more often, the customers enjoy also a foot and a facial massage.